The Breast Cancer Genes - Haque, MM; Sarkar, S; Mallick, AK (TAJ: Journal of Teachers Association, 2009)
Breast cancer, almost exclusively a disease of the women, accounts for 10% of 10 million new cancer cases each year and causes 370,000 deaths annually although the incidence in Asia is low. Risk factors for breast cancers belong to different domains. Those associated with the highest relative risk belong to the genetic domain. The only group of women with mutated breast cancer genes had an average lifetime risk of developing breast cancer was calculated to be 65.3%. Genetic counseling and genetic study might help surgeons as well as the patients to better estimate the risk of developing breast cancer disease. doi: 10.3329/taj.v17i2.3461 TAJ 2004; 17(2): 117-120